Studi Kelayakan Penggunaan Sel Surya Dengan Sistem Off-Grid Pondok Pesantren Sidrotul Muntaha - Wijaya, Ibrahim Fatwa, Hasyim Asy'ari, ST.MT (2017)
Sidrotul Muntaha boarding school is a great place to study and deep the religious knowledge. In this boarding school construction certainly is not detached from the needs of electrical energy to support students activities. The boarding school is located in the corner of the area that have already been electrified by State Electricity Company but still with small power, so that renewable energy is needed to make a power plant. The selected renewable energy utilization is harnessing the suns light energy is often called Solar Power Plant. Sunlight can be converted into electrical energy used solar cells are made of semiconductor material that has particles of electrons and protons. Solar cells can absord sunlight containing electromagnetic waves that are capable of generating kinetic energy to release electrons into conduction bands to produce electrical energy. This Solar Power Plant design uses off-grid system because in the operation is not connected to the State Electricity Company electricity network. This design aims to determine the total of Wh (Watt Hours) per day by doing interviews to users about the burden that is mounted and the duration of its use, determine the amount of solar cells, the number of battery, and the number of point lights are needed. The results of the design show that the total Wh per day is 68862,43 Wh, with 2 V 1100 Ah battery capacity amounted to 120 units, 5000 W inverter capacity amounted to 2 units, and the number of solar cell is 108 module with 200 Wp (Watt Peak) maximum power so that the Solar Power Plant capacity is 108 x 200 Wp = 21.600 Wp or 21,6 kWp. Key Words : Solar Power Plant, Solar cell, Off-Grid, Inverter, State Electricity Company .